Analysis of Pb and Zn pollutant concentration in the water, sediment and the meat of Cerithidea obtusa from the Tanjung Pasir Village, Tanah Merah Sub-District, Indragiri Hilir Regency, Riau Province - Rizki Syawalia Siregar; Budijono '; Eko Purwanto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The Nyiur and Enok Rivers merged and form a single river mouth in the Tanjung Pasir Village. Around the river mouth, however, many industrial and shipping activities may produce Pb and Zn pollutant that enter the water, accumulated in the sediment as well as in the meat of benthic organisms such as Cerithidea obtusa. To understand the concentration of Pb and Zn in the water, sediment and the snail, a research has been conducted on March 2017. There are 3 stations, around 3 km before the outlet of PT Sambu, in the outlet of PT Sambu and 3 km of PT Sambu. Samplings were conducted 3 times, once/ 2 days. Results shown that the highest concentration of Pb and Zn in water (0.0543 mg/L and 0.1767 mg/L), sediment (1.7469 ppm and 3.2720 ppm) and C. obtusa (4.9085 mg/kg and 8.1990 mg/kg) was in the station II. Keyword : Cerithidea obtusa, pollutant, sediment, Tanjung Pasir Village